2022
DOI: 10.1088/1741-4326/ac5d62
|View full text |Cite
|
Sign up to set email alerts
|

Toroidal modeling of runaway electron loss due to 3D fields in ITER

Abstract: Mitigation of runaway electrons (REs) by three-dimensional (3-D) magnetic field perturbations is numerically investigated for the ITER 15 MA baseline D-T scenario, utilizing the MARS-F code [Liu et al Phys. Plasmas 7 3681] with a drift orbit test particle tracing module. Considered are two types of 3-D fields: the n=3 (n is the toroidal mode number) resonant magnetic perturbation (RMP) utilized for the purpose of controlling the edge localized modes in ITER, and perturbations generated by the n=1 magneto-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Experiments aimed at mitigating tokamak disruptions with massive material injection (gas or pellets) have long sought unsuccessfully to exceed the socalled Rosenbluth density to maintain E < E crit even at post-TQ temperatures [3][4][5]. Injection of either high-Z (Ne, Ar, Kr, Xe) [6,7] or low-Z (He, D 2 ) [7,8] material into an existing RE beam has also been pursued, with D 2 injection showing strong promise experimentally for benign termination of a RE beam by a kink instability, supported by extendedmagnetohydrodynamic (MHD) modeling [9][10][11], which has been extended to ITER scenarios [12]. Strategies to prevent the formation of a mature RE beam involve enhancing transport of the seed REs in physical or momentum space, e.g., by stochastic magnetic fields [13][14][15][16][17][18] or wave-particle interactions [19,20], to produce a loss rate that exceeds the avalanche growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments aimed at mitigating tokamak disruptions with massive material injection (gas or pellets) have long sought unsuccessfully to exceed the socalled Rosenbluth density to maintain E < E crit even at post-TQ temperatures [3][4][5]. Injection of either high-Z (Ne, Ar, Kr, Xe) [6,7] or low-Z (He, D 2 ) [7,8] material into an existing RE beam has also been pursued, with D 2 injection showing strong promise experimentally for benign termination of a RE beam by a kink instability, supported by extendedmagnetohydrodynamic (MHD) modeling [9][10][11], which has been extended to ITER scenarios [12]. Strategies to prevent the formation of a mature RE beam involve enhancing transport of the seed REs in physical or momentum space, e.g., by stochastic magnetic fields [13][14][15][16][17][18] or wave-particle interactions [19,20], to produce a loss rate that exceeds the avalanche growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…[6] we expect the electron inertia terms in the generalized Ohm's law to become relevant in the sublayer physics found in this regime. A further step of this work will be to consider multiple helicity reconnection modes introducing magnetic field lines stochasticity expected to play a significant role in the runaway electron dispersion [14,15].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In the horizon of scientific research on the problems of simulation of electrons and electron-related processes, it is worth noting the studies by C. Lamy (on the possibility of using artificial neural networks for modelling non-local electron transport in plasma) [1], B. Tang (on numerical modelling of the processes of suprathermal electron transport in the solar wind) [2], X. An (on modelling the effects of bound electrons in the process of model studies of particles in a cell) [3], Y. Liu (on toroid modelling of electron loss processes flowing out of a 3D field in the organisation of research in the international experimental thermonuclear reactor (ITER)) [4], X. Li (on modelling the processes of acceleration and electron transfer in the early pulsed phase of a solar flare) [5], "Modelling of non-local electron transport in laser-driven double-ablation fronts" [6], "Relaxation of electron beams/strahls in solar outflows: observations vs. modelling" (on the correlated analysis of the results of modelling and full-scale measurements of electron beam/strahl relaxation processes in solar flows) [7], H. Funaba (on the study of the Thomson scattering effect in modelling and estimating electron temperature) [8], D. Vatansever et al (on modelling surfaces that emit electrons when boundary layers are immersed in plasma) [9], V. Lazurik (on the investigation of semi-empirical models of electron beam control in radiation technologies) [10], O. Linder (on self-matching modelling of electron run-up during breakdowns in Tokamak (ITER)) [11], L. Adhikari (on modelling the process of heating protons and electrons in a fast solar wind) [12], M. Wibowo (on modelling the dynamics of ultra-fast electrons in strong magnetic fields using real-time electronic structure methods) [13], Y. Huang (on modelling strong electron heating by radio frequency waves at EAST) [14], Z. Wang (on real-time modelling and estimation of the total electron content in the vertical global ionosphere using hourly IGS data) [15]. When analysing these specialised publications, it was found that in modern physics, electron models only describe its properties.…”
Section: Introductionmentioning
confidence: 99%